Hábitat y abundancia de Coturnicops notata y Porzana spiloptera en Mar Chiquita, prov. de Buenos Aires, Argentina - Matinez, Mariano Manuel (1997)
We provide new records, data on habitat and abundance of the Speckled Crake (Coturnicops notata) and Dot-winged Crake (Porzana spiloptera), and measurements and stomach contents of one C. notata. The study area was Mar Chiquita Reserve, Buenos Aires Province. Records were gathered as follows: between 1983-84, 1992-97 during monthly censuses at different habitats (but mainly on grassland), and in 1995-96 during 1000 m transects in grasslands of Spartina densiflora and Juncus acutus (c1imax state and postfire succession). The Speckled Crake was recorded in four opportunities, on three different habitats: grasslands of S. densiflora, J. acutus and a patch of Scirpus americanus. The Dot-winged Crake was recorded in 26 opportunities (41 individuals), two on J. acutus grassland and the rest on mature grassland of S. densiflora. The Speckled Crake has a wider distribution, it's apparently more plastic in habitat requirements but rarer; the Dot-winged Crake has a narrower distribution, it's habitat specific (occurs mostly with S. densiflora), and locally more frequent (but uncommon).